Water-centered growth challenges, innovations and interventions in Ethiopia - Awulachew, Seleshi Bekele (2011)
Ethiopia?s economy and majority of the people?s livelihoods are dependent on agriculture. To develop the socioeconomy of Ethiopia and eradicate poverty, the policy and interventions should focus on agriculture as an entry point. In line with this, the government, bilateral and multilateral donors, NGOs and various institutions share the concepts and priorities identified in the ?Plan for Accelerated and Sustained Development to End Poverty (PASDEP).? There are key challenges that need to be strongly addressed on transforming agriculture by overcoming a multitude of problems including biophysical and water management issues to help achieve the targets of PASDEP and sustainable socioeconomic growth in Ethiopia. This particular paper aimed at addressing the water management challenges that Ethiopia has faced in the past and is facing today, and to stimulate ideas on how to manage water resources to meet the growing needs for agricultural products, to help reduce poverty and food insecurity, and to show how water can be used as an important entry point to transform its socio-economy and contribute to sustainable development and the environment. The issues discussed will focus on innovations, policies and technologies that enable better investment and management decisions in water use, particularly focusing on agriculture and irrigation but also briefly looking into other water-related subsectors such as hydropower, water supply, watershed, drought and flood management as well as other biophysical aspects. It has also been attempted to make the paper suitable for decision-makers rather than scientists, in order to raise useful ideas for dialogue and further discussions, studies and researches. The paper, therefore, does not claim exhaustiveness. The target audiences of this paper are the people who make the investment and management decisions in water and water management for agriculture, and other subsectors - agricultural producers, water managers, investors, policymakers and civil society. The paper has benefited from the review of key policy and strategy documents of Ethiopia, outputs of various outcomes of research, civil society meetings and workshops, data and information available in government institutions, and global knowledge. The key major issues that are discussed in the paper include the following: Socioeconomic development challenges of Ethiopia, viewed from a water resources perspective., The water resources endowment, development extent, potentials and economic/socioeconomic development linkages., Water-related innovations and agriculture., Water-related interventions in various agro-ecologies., Policy and strategy actions needed. This paper should also be viewed with other components such as river basin growth pole/corridor concept, institutional reform and research capacity building. It focuses on analyzing key problems and associated interventions, and can be applicable in the contexts of the current situation and the future possible reform under growth zones that can be taken as plausible pathways for development.